Hiatal hernia size, Barrett’s length, and severity of acid reflux are all risk factors for esophageal adenocarcinoma - Avidan, Benjamin; Sonnenberg, Amnon; Schnell, Thomas G; Chejfec, Gregorio; Metz, Adrienne; Sontag, Stephen J (The American journal of gastroenterology, 2002)
OBJECTIVE: The reasons for the development of dysplasia and adenocarcinoma in Barrett’s mucosa are not well understood. The aims of this study were to characterize risk factors for the transition from Barrett’s esophagus without dysplasia to Barrett’s esophagus with high-grade dysplasia or esophageal adenocarcinoma. METHODS: A group of 131 patients with high-grade dysplasia or esophageal adenocarcinoma were selected as case subjects. A first population of 2170 patients without gastroesophageal reflux disease (GERD) and a second population of 1189 patients with Barrett’s esophagus served as two control groups. Logistic regression analyses were used to compare the risk factors associated with the occurrence of high-grade dysplasia or esophageal adenocarcinoma. RESULTS: Patients with high-grade dysplasia or esophageal adenocarcinoma shared many characteristics with other forms of severe GERD, such as older age, male gender, and white ethnicity. The length of Barrett’s esophagus and the size of hiatus hernia increased the risk for both conditions. Subjects with high-grade dysplasia and adenocarcinoma had more severe acid reflux than patients with other forms of GERD. Smoking and alcohol consumption did not affect the risk for developing high-grade dysplasia or adenocarcinoma in patients with Barrett’s esophagus. CONCLUSIONS: High-grade dysplasia and esophageal adenocarcinoma seem to stem from an extreme and unfavorable constellation of all risk factors that are generally held responsible for the development of GERD and Barrett’s esophagus.